(untitled) - Fernandez Araoz, Claudio (Hoboken, N.J., 2007)
Fernandez-Araoz provides compelling evidence for why making great people decisions is essential for anyone who aspires to become a great leader or build a great company. If you follow the sage advice he offers in this book, you are sure to make great people decisions
Keywords: Executives,Executive ability,Employee retention,Organizational effectiveness,Nhân viên điều hành,Khả năng điều hành,Giữ lại nhân viên,Hiệu quả tổ chức; Recruiting,Evaluation,Tuyển dụng,Đánh giá